Clinico-dermoscopic features and treatment responsiveness in pediatric alopecia - Experience from a tertiary care pediatric dermatology clinic - Rahul Mahajan; Manju Daroach; Dipankar De; Sanjeev Handa (Wolters Kluwer Medknow Publications, 2020)
Background: Data on clinical and epidemiologic profile on pediatric alopecia is relatively scarce. Aims and Objectives: We aimed to study the clinical, epidemiological, and dermoscopic profile of children presenting with alopecia, and assess the responsiveness to different treatment modalities in a real-life setting. Materials and Methods: This cohort study involved analyzing children presenting with hair loss during the study period. After a detailed history, clinical, and trichoscopic examination, treatment offered to patients and follow-up response to treatment along with relapse of symptoms were noted. Results: Around 119 children were included. Nearly 90% were of acquired etiology. The most common cause of alopecia was alopecia areata (AA) in 85 (71%) patients followed by tinea capitis 9 (7.5%), lichen planopilaris 4 (3.3%), and other less common causes. In patients of AA, dermoscopy showed the presence of black dots in 68% cases, exclamation mark hair in 54% of patients followed by off-white dots, yellow dots, and vellus hair. Patients with an acute course and black dots on dermoscopy responded better to treatment. Relapse was common in patients with early age of onset and longer disease duration. Conclusions: Hair loss is frequently seen in pediatric dermatology clinics. Dermoscopy of pediatric AA shows scarce yellow dots while off-white dots are more frequent; the presence of black dots is a good prognostic indicator.